A Mandibular First Molar with Three Distal Canals: A Case Report and Literature Review - Beyraghshamshir, Reza; Zarei, Mina; Sekandari, Salehe (Iranian Endodontic Journal, 2019)
For a successful root canal treatment, it is critical for a clinician to have complete knowledge of the root canal morphology. There are numerous cases in literature concerning the unusual anatomy of mandibular first molars. This report presents a case of a mandibular first molar with three distal canals. An overview of the types and numbers of the common anatomic forms of this tooth also is presented, as is a summary of published anomalies. Key words: Distal Root; Mandibular First Molar; Root Canal Anatomy